2019
DOI: 10.1002/ppsc.201900233
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Operation of Photovoltaic Optoelectronic Tweezers: New Strategies for Massive Nano‐object Manipulation and Reconfigurable Patterning

Abstract: Optical and optoelectronic techniques for micro‐ and nano‐object manipulation are becoming essential tools in nano‐ and biotechnology. Among optoelectronic manipulation platforms, photovoltaic optoelectronic tweezers (PVOTs) are an emergent technique that are particularly successful at producing permanent nanoparticle microstructures. New strategies to enhance the capabilities of PVOT, based on real‐time operation, are investigated. This optoelectronic platform uses z‐cut LiNbO3:Fe substrates under excitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Better knowledge of the surface structure and its properties (including oxygen vacancies) [22,52] would offer the possibility of nanoscale devices, molecular detection, and efficient catalysts [54], among other applications. This remark is of special relevance in relation to real-time operation of optoelectronic (photovoltaic) tweezers in LiNbO3 and will advance our understanding of the trapping and untrapping cycles during their operation [55]. Furthermore, recent publications can be found in the literature showing potential applications in neuromorphic computing through the production of oxygen vacancies in LiNbO3 thin films by Ar + irradiation [56].…”
Section: Discussionmentioning
confidence: 78%
“…Better knowledge of the surface structure and its properties (including oxygen vacancies) [22,52] would offer the possibility of nanoscale devices, molecular detection, and efficient catalysts [54], among other applications. This remark is of special relevance in relation to real-time operation of optoelectronic (photovoltaic) tweezers in LiNbO3 and will advance our understanding of the trapping and untrapping cycles during their operation [55]. Furthermore, recent publications can be found in the literature showing potential applications in neuromorphic computing through the production of oxygen vacancies in LiNbO3 thin films by Ar + irradiation [56].…”
Section: Discussionmentioning
confidence: 78%
“…First preliminary results on light-induced ejection of Ag nanoparticles from a PV crystal were presented in a previous publication, which was focused on real-time operation of PVOT. [19] Figure 3 shows several experimental results that summarize the observed behavior. After deposition of a uniform background of Ag particles dispersed in heptane on a z-cut LN:Fe crystal, the PV substrate was excited by a focused Gaussian beam (see the Experimental Section).…”
Section: Light-induced Ejection Of Particles From Linbo 3 :Fe Surfacesmentioning
confidence: 93%
“…In ref. [19], where preliminary data on the ejection phenomenon with Ag nanoparticles were reported, it was suggested that this effect might occur due to a charge transfer between the illuminated PV ferroelectric crystal and the particles. According to this proposal, particles get charged with the same sign as the corresponding polar face (negative at the +c face and positive at the −c face), leading to Coulomb repulsion and ejection (see Figure 7a).…”
Section: Charge Transfer Between the Ferroelectric Crystal And Micro-...mentioning
confidence: 99%
See 2 more Smart Citations